(untitled) (Economics and region, 2016)
The essence and peculiarities of implementation benchmarkenhu. Obhrunovano necessity and advantages of benchmarking in industrial activities in Ukraine. Accelerated strengthening and increased competition caused by the process of active development of the market environment and the globalization of the world economy makes the current domestic enterprise to compete with the best companies not only in the domestic but also foreign markets. Under such conditions the company must constantly monitor their own strengths and weaknesses, and find ways to strengthen competitive advantages, identify and mitigate the impact of the causes of inefficiency of market activity, identify and implement strategic measures. One of the analytical tools of standard tests, solving the problems identified and of market strategies is benchmarking. Therefore appropriate presents a detailed study, study and application of the concept of benchmarking domestic industry and use the results to improve performance, gaining competitive advantage, securing positions on the markets. Today in Ukraine there are a number of problems related to the competitiveness of domestic products in the world market of goods and services, and at the same time - a small range of options to improve the alarming trends in recent years. Relevance of the research promising ways to obtain competitive advantage is critical in a time of economic turmoil in the world in general and in Ukraine in particular. If the economy will recover and grow even bigger than before the crisis, it will allow companies to reach a new level of competitiveness. Therefore, an important condition for effective foreign business entities in the internationalized market environment is the introduction and use of new, more efficient and more effective management and analysis of international competitiveness, aimed at improving the forms of international business. One of these methods is benchmarking, which aims to reliably based on studies establish the likelihood of success on the international stage. Benchmarking is an important tool, especially in situations where it is necessary to review the internal efficiency of the company and identify new priorities. Comparison of performance helps to understand the sensitive and rational aspects of the company compared to competitors and world leaders in a similar field. This allows you to find unfilled niches, go to probable partners from industrial and technical cooperation and find out the benefits of the merger. Benchmarking analysis can lead to increased profitability of business with high profitability, creating competition and efficiency to meet the needs of customers. Therefore, the introduction of benchmarking in practice Ukrainian industry is a guarantee of strengthening their competitive position in the domestic market as well as the condition of full and effective entry into the world economy.